(untitled) (Islas, 2022)
ABSTRACT: Introduction: The ecphrastic practices related to the visual arts find a space for the reeducation of perspectives through the works of the artist Geovanny Verdezoto; who warns and subverts, with audacity, intercultural and inclusive experiences on his canvas: a representation that invites critical reflection and verbal rehearsal. Methods: On this occasion, we have considered a methodology that assumes essential features of the qualitative approach, from the social constructionist perspective, the hermeneutical method and techniques such as observation, self-report and interview. Results: The work of this forger does not emerge as mere entertainment, it is an allegory and iconic expression of the legacy of those who advocate for the emancipation of the universal human being. Therefore, it is worth finding the way in which the poetics of the creator configures and dialogues to transmit messages that favor the aggrandizement of the person (learner). Conclusions: This work constitutes an intellectual and moral exercise that invites the acceptance of the multiplicity and differences in the pedagogical and andragogical settings.